If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 = -50 + -4x Reorder the terms: 6 + 4x = -50 + -4x Solving 6 + 4x = -50 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 4x + 4x = -50 + -4x + 4x Combine like terms: 4x + 4x = 8x 6 + 8x = -50 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 8x = -50 + 0 6 + 8x = -50 Add '-6' to each side of the equation. 6 + -6 + 8x = -50 + -6 Combine like terms: 6 + -6 = 0 0 + 8x = -50 + -6 8x = -50 + -6 Combine like terms: -50 + -6 = -56 8x = -56 Divide each side by '8'. x = -7 Simplifying x = -7
| 9+3(x+2)=21 | | a*5+71=a*9-5 | | 2(q+3)=1 | | 8y-2=-8 | | -22+7= | | 0.625x+0.75=7 | | 8+-7= | | 3(x+1)+7(x+3)=64 | | 23-(7)= | | 8a(4b)(4)= | | -22-(7)= | | F(x)=x^2+6x+34 | | X+4=3+3x | | 2x^2-46= | | 7(k-3)=3k-6 | | (34)3=3 | | z=b-y | | 3x+50=6x-25 | | 7x-1=4x+1 | | Y-(12)=5 | | 9h+7=97 | | -2+1=m-8 | | 25x-9x^3=0 | | 2(-x-3)*7-3x=-8 | | 8x+9=4x+53 | | 10m-27=43 | | 2(-x)*7-3x=-8 | | 6(v+4)-2v=2(2v+1)-6 | | 36=3x(18-3x) | | x+19=39 | | 15x^4+84x^2-36=0 | | 5x^2+19x+15=0 |